An Overview of Aggressive Behaviors in Children with Autism Spectrum Disorder - Satopoh, Flavia Angelina (Scientia Psychiatrica, 2024)
Children and adolescents with autism spectrum disorder (ASD) frequently exhibit symptoms of irritability and aggression, which may appear as tantrums, self-injury, and violent behaviors. As a result, parents often bring their children to the emergency room or seek psychiatric treatment. Aggression refers to conduct that poses a threat or inflicts injury by bodily or verbal actions, such as striking, biting, hurling things, or using offensive language against another individual. Aggressive behaviors can detrimentally impact the patient's quality of life, increase their stress levels, and hinder their ability to get educational and social assistance. A multidisciplinary approach is crucial for assessing patients and selecting the most effective treatment. Both non-pharmacologic and pharmacologic treatments are available to address violent behavior in children with ASD. As a health practitioner, it is crucial to understand the circumstances that might trigger aggressiveness in children with ASD and possess the knowledge and skills to effectively manage and treat these patients. By doing so, we can optimize their outcomes and enhance their overall quality of life.